Marketing Campaign Insight in Open and Distance Learning Higher Education from Internet Analytic - Rahmat Budiman; Abdurrahman Rahim Thaha; Gunawan Wiradharma (JINAV: Journal of Information and Visualization, 2023)
This study aims to find marketing campaigns that match the interests of the online audience at the Universitas Terbuka (UT) as an Open and Distance Learning (ODL) institution in Indonesia. Keyword research is used as a research method with the help of the keyword everywhere tool to get insights from keywords. Universitas Terbuka has high internet searches, indicating a high level of audience interest. Area and academic themes became the highest audience interest in the June-August range. Universitas Terbuka can create and schedule content based on keyword research findings. This research provides insight into a practical marketing plan that can be made based on keyword research so that it is effective and in the interests of the audience on the internet.